Legal Review of the Issuance of Blank Bilyet Giro - Putri, Qonita Rizqi Iffani; Gunadi, Ariawan (Universitas Semarang, 2024)
The purpose of this research is to find out clearly about the Legal Review of Issuing Blank Bilyet Giro. checks and giro bills in commercial transactions that can give rise to legal consequences. Depending on their nature, unlawful acts can be classified as criminal or civil offenses. Therefore, depending on the circumstances, the use of checks and giro bills in commercial transactions can be classified as a civil or criminal offense. The research methodology chosen is descriptive research (descriptif research), which is part of concept-based criminological research. Additional legal impacts may result in criminal and civil penalties. Reasons and Steps for Surrendering a Bilyet Giro. The interested bank is obliged to reject the Bilyet Giro offered by the holder if it turns out to be empty and the available funds are insufficient. The refusal must be accompanied by a Certificate of Rejection (SKP) which, among other things, must include the full name and address of the party making the withdrawal.